Perceived access to social support during and after TB treatment in Mbeya and Songwe regions, Tanzania: perspectives from TB patients and survivors set against health care providers - Kilima, Stella P.; Mubyazi, Godfrey M.; Moolla, Aneesa; Ntinginya, Nyanda E.; Sabi, Issa; Mwanyonga, Simeon P.; Evans, Denise (Frontiers in Health Services, 2024)
IntroductionPulmonary tuberculosis (PTB) remains a life-threatening disease in Tanzania, with negative physical, financial, economic and psychosocial consequences to individuals and the society. It mainly lowers the quality of life of patients, survivors and their families, especially those in the poorest and socially deprived categories.ObjectivesTo report and discuss a qualitative study that assessed the nature of social support desired and received by PTB patients and survivors. Participants were given a chance to share their experiences and their perceptions on whether the social support they desired had an impact on their treatment-seeking behaviour and treatment adherence.MethodsFace-to-face interviews were conducted with the three aforementioned groups, purposively selected at a TB clinic between October 2020 and March 2021. The questions covered topics related to the types of social support desired and the sources of support during and after treatment, if any. Interviews were concluded until no new information was obtained. Data analysis was facilitated using NVivo 12 software.ResultsParticipants pointed out a need for psychosocial, financial, and material support during and after treatment. However, they sometimes miss support from family/household members or the rest of the community. Because of this experience, they lived with difficulties, facing hardships when required to pay out of pocket for transport during the care-seeking. Survivors testified experience of a denial of support by even their close relatives who regarded them as no longer needing it after recovering. Patients and survivors also reported experience of social isolation as they were believed able to transmit PTB infections. Limited psychological support at the contacted TB clinics was another experience reported. TB clinic staff's experiences confirmed almost all the experiences shared by their clients. With limited support, resilience and self-care were identified as key mechanisms for coping.ConclusionComplete recovery from PTB is possible, but reverting to a normal life is difficult without social support. Policies and programs need to increase opportunities for social support for TB patients and survivors. Doing so is likely to improve TB-related treatment, care-seeking practices, and adherence.